The man who loved China : [compact disc, unabridged] : the fantastic story of the eccentric scientist who unlocked the mysteries of the Middle Kingdom - Winchester, Simon (Harper Audio, 2008)
Biography of Joseph Needham, a Cambridge scientist who turned his eccentric genius on the study of China. He produced seventeen immense volumes on China, marking him as the greatest one-man encyclopaedist.